Seismic while drilling experiment with diamond drilling at Brukunga, South Australia - Sun, Bai Chun; Bona, Andrej; Zhou, B.; King, A.; Dupuis, Christian; Pevzner, Roman (CSIRO, 2013)
Seismic-While-Drilling (SWD) utilises drill bit vibrations as a seismic source and receivers at the surface or in a borehole to acquire reverse VSP data. The basic processing technique is based on cross correlation to generate active shot-gather-like profiles. The successful implementation of SWD will yield time-depth information and image around the drill bit, which can aid drilling and geological understanding of the area. To study the feasibility of using diamond impregnated drill bits for seismic-while-drilling, we conducted a small pseudo 3D SWD experiment at Brukunga, South Australia. It has been used to investigate the signals generated from diamond drilling, and study the potential to use a drill bit as a seismic source. The drill bit energy for seismic imaging is influenced by the rig power setting, and the state of the drill bit (new or worn bit). The experiment shows that normally the diamond drilling frequency band is wide with strong discrete peaks, however sometimes due to changes in the drilling mode, e.g., increase or decrease the drilling power, the frequency spectrum can be smoothed. The strong peaks in the spectrum mean strong periodicity of the signal and as such, the signals do not lend themselves to standard cross correlation. Thus, we use a generalised cross correlation that produces results similar to an active shot gather-like profile.